Polyester resins and articles made therefrom
By controlling the polymer raw material composition of polyester resin, especially the molar ratio of 1,4-cyclohexanedimethanol and trans-1,4-cyclohexanedimethanol, the problems of insufficient heat resistance and mechanical strength of polyester resin are solved, and polyester resin products with high heat resistance, mechanical strength and low greenhouse gas emissions are achieved.
Patent Information
- Application Number
- CN202480001448.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-01-11
- Filing Date
- 2024-03-12
- Publication Date
- 2025-09-12
AI Technical Summary
Existing technologies make it difficult to simultaneously improve the heat resistance and mechanical strength of polyester resins. There are also problems with increased manufacturing costs and diminished color characteristics, and plastic products emit large amounts of greenhouse gases at each stage.
By controlling the polymerization raw materials of the polyester resin, especially using a specific diol composition, such as the molar ratio of 1,4-cyclohexanedimethanol and trans-1,4-cyclohexanedimethanol, the tan δ peak temperature and strain recovery rate are controlled to prepare a polyester resin with high heat resistance and mechanical strength.
The polyester resin achieves rapid strain recovery at high temperatures, improves heat resistance and mechanical strength, reduces greenhouse gas emissions, and prepares environmentally friendly polyester resin products.
Smart Images

Figure BDA0004963429830000181 
Figure BDA0004963429830000191 
Figure BDA0004963429830000192
Abstract
Description
Technical Field
[0001] The present invention relates to a polyester resin having excellent recovery properties from strain occurring at high temperatures and thus having high heat resistance and mechanical strength, and to a product prepared using the polyester resin. Background Art
[0002] Among polymers, polyester resins are widely used as materials for beverage or food containers, various packaging films or sheets, indoor and outdoor materials such as panels, shelves, and partitions, and the like.
[0003] In particular, polyester resins used to manufacture articles such as food containers and packaging films are required to have high heat resistance and mechanical strength. In particular, articles manufactured from polyester resins must have heat resistance at a level that allows them to be used in microwave ovens and dishwashers operating at high temperatures, and impact strength to a degree that prevents them from breaking even when subjected to external impact.
[0004] In order to improve the heat resistance and mechanical strength of polyester resins, technologies have been proposed to blend polyester resins with other resins or add specific additives thereto. However, these technologies have limitations in simultaneously enhancing the heat resistance and mechanical strength of polyester resins and cause problems such as increased manufacturing costs, reduced processing efficiency, and loss of color characteristics (e.g., transparency).
[0005] Therefore, there is a need to develop a technology that can effectively improve the heat resistance and mechanical strength of polyester resins.
[0006] Plastic products made from polyester resins and other materials also emit greenhouse gases during the procurement, manufacturing, distribution, use, and disposal stages of raw materials. Since these greenhouse gases are a major cause of global warming, environmentally friendly plastics technologies are needed to reduce the amount of greenhouse gases produced. Summary of the Invention
[0007] Technical issues
[0008] Unlike conventional techniques that involve blending different resins or using specific additives, the present inventors have discovered that polyester resins with high heat resistance and mechanical strength can be obtained by simply controlling the polymeric raw materials used in the polyester resin. Specifically, they have discovered that using a specific diol composition during the polyester resin production process allows the polyester resin to rapidly recover from strain when exposed to high temperatures, significantly improving both its heat resistance and mechanical strength. Furthermore, using this specific diol composition allows for the production of polyester resins with minimized greenhouse gas emissions.
[0009] Therefore, an object of the present invention is to provide an environmentally friendly polyester resin having excellent recovery characteristics from strain occurring at high temperatures and thus having high heat resistance and mechanical strength, and to provide an article prepared using the polyester resin.
[0010] Solution to the problem
[0011] To achieve the above object, the present invention provides a polyester resin comprising a diol repeating unit derived from a diol component; and a dicarboxylic acid repeating unit derived from a dicarboxylic acid component, wherein when the value of tan δ is measured by dynamic mechanical analysis (DMA), the temperature at the maximum value of tan δ (tan δ peak) is 100° C. or higher, and the following Equation 1 is satisfied:
[0012] [Equation 1]
[0013] 30≤X×Y≤60
[0014] In Equation 1, X is the mole percentage of 1,4-cyclohexanedimethanol (CHDM) based on 100 mol% of the diol component, and Y is the molar ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) to 1,4-cyclohexanedimethanol (CHDM).
[0015] Furthermore, the present invention provides an article prepared from the polyester resin.
[0016] Beneficial effects of the present invention
[0017] When the polyester resin according to the present invention is obtained by using a diol component containing 1,4-cyclohexanedimethanol having a specific composition as a polymerization raw material, its physical properties are controlled within specific ranges (i.e., X×Y, tan δ peak temperature, strain recovery rate (SR), T m , impact strength, etc.). Therefore, it has excellent properties of recovering from strain occurring at high temperatures, so it can have high heat resistance and mechanical strength, as well as excellent moldability. In addition, when the polyester resin according to the present invention is obtained by using a diol component containing isosorbide as a polymerization raw material, it is possible to minimize the emission of greenhouse gases such as carbon dioxide (CO2) during the production of products and the use and disposal of the products.
[0018] Therefore, when an article is manufactured using the polyester resin according to the present invention, an environmentally friendly article having excellent heat resistance and mechanical strength can be efficiently produced.
[0019] Best Mode for Carrying Out the Invention
[0020] The present invention will be described in detail below. The present invention is not limited to the disclosure given below, but it can be modified in various forms as long as the gist of the present invention is not changed.
[0021] In this specification, the term "comprising" is intended to specify specific characteristics, regions, steps, processes, elements and / or components. Unless explicitly stated otherwise, the existence or addition of any other characteristics, regions, steps, processes, elements and / or components is not excluded.
[0022] Throughout this specification, the terms first, second, etc. are used to describe various components. However, these components should not be limited by these terms. These terms are used to distinguish one element from another.
[0023] Unless otherwise indicated, all numbers and expressions relating to quantities of ingredients, reaction conditions, and so forth used herein are to be understood as modified by the term "about."
[0024] In this specification, unless otherwise indicated in the context, expressions in the singular are construed as including the plural as well.
[0025] polyester resin
[0026] The polyester resin according to the present invention comprises a diol repeating unit derived from a diol component; and a dicarboxylic acid repeating unit derived from a dicarboxylic acid component, wherein when the value of tan δ is measured by dynamic mechanical analysis (DMA), the temperature at the maximum value of tan δ (tan δ peak) is 100° C. or higher, and satisfies the following Equation 1:
[0027] [Equation 1]
[0028] 30≤X×Y≤60
[0029] In Equation 1, X is the mole percentage of 1,4-cyclohexanedimethanol (CHDM) relative to 100 mol% of the diol component, and Y is the molar ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) to 1,4-cyclohexanedimethanol (CHDM).
[0030] Equation 1 shows the correlation between the molar percentage of 1,4-cyclohexanedimethanol in the total diol component and the molar ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) in the 1,4-cyclohexanedimethanol. In the polyester resin according to the present invention, the value (X×Y) obtained by multiplying the molar percentage by the molar ratio (excluding units) falls within the range of 30-60. Specifically, X may refer to the molar percentage of 1,4-cyclohexanedimethanol contained in the diol component based on 100 mol% of the diol component, and Y may refer to the ratio of the amount of trans-1,4-cyclohexanedimethanol contained in the total amount of 1,4-cyclohexanedimethanol.
[0031] If the value of X×Y in Equation 1 is less than 30 or greater than 60, the glass transition temperature (T g ) and melting point (T m ) does not reach the required level, so it is impossible to obtain a polyester resin having high heat resistance and excellent moldability, and it is impossible to achieve enhancement of the mechanical strength and processability of the polyester resin. However, since the polyester resin according to the present invention satisfies the above equation 1, it can have high heat resistance and mechanical strength, as well as excellent moldability.
[0032] According to the present invention, the value of X×Y in Equation 1 can specifically be 31 or more, 32 or more, 33 or more, 35 or more, 38 or more, 40 or more, 43 or more, 45 or more, 48 or more, 50 or more, or 52 or more, and 59 or less, 57 or less, 55 or less, 52 or less, 50 or less, 48 or less, 45 or less, 43 or less, 40 or less, or 35 or less (e.g., 31 to 59, 32 to 59, 33 to 58, 33 to 57, 34 to 55, 35 to 54, 36 to 52, 38 to 50, or 40 to 47).
[0033] According to the present invention, in the polyester resin, when the value of tan δ is measured by dynamic mechanical analysis (DMA), the temperature at which the maximum value of tan δ (tan δ peak) is reached may be 103° C. or higher, 105° C. or higher, 108° C. or higher, 110° C. or higher, or 113° C. or higher, and 120° C. or lower, 118° C. or lower, 116° C. or lower, or 115° C. or lower (e.g., 100° C. to 120° C., 101° C. to 119° C., 102° C. to 119° C., 104° C. to 118° C., 107° C. to 117° C., 108° C. to 116° C., or 110° C. to 115° C.). When the temperature at which the maximum value of tan δ (tan δ peak) is reached within the above range, a polyester resin having high heat resistance can be provided.
[0034] According to the present invention, when the polyester resin is analyzed by differential scanning calorimetry (DSC), its melting point (T m ) may not appear (may not be measurable). Alternatively, the polyester resin may have a melting temperature (T m In particular, the melting temperature (T m ) may be 248°C or lower, 246°C or lower, 244°C or lower, 242°C or lower, 240°C or lower, 238°C or lower, or 235°C or lower (e.g., 225°C to 250°C, 230°C to 250°C, 231°C to 249°C, 233°C to 248°C, 234°C to 247°C, or 235°C to 245°C). When the melting point (Tm ) does not appear or is 250°C or lower, the moldability and heat resistance of the polyester resin can be ensured. Specifically, if the melting point (T m ) exceeds 250°C, the crystallinity of the polyester resin may become too high, and thus the moldability may be significantly reduced. Therefore, the melting point (T m ) is preferably 250°C or lower.
[0035] Here, when the melting point (T m ) when the melting point (T m ) can specifically be 30 J / g or less, 25 J / g or less, 23 J / g or less, 20 J / g or less, 18 J / g or less, 15 J / g or less, 13 J / g or less, 10 J / g or less, or 5 J / g or less (e.g., from greater than 0 J / g to 30 J / g, from 1 J / g to 25 J / g, from 2 J / g to 20 J / g, from 3 J / g to 15 J / g, or from 5 J / g to 13 J / g).
[0036] In addition, when the polyester resin is analyzed by differential scanning calorimetry (DSC), its glass transition temperature (T g ) can exceed 100°C. In particular, the glass transition temperature (T g ) may be 101° C. or higher, 102° C. or higher, 103° C. or higher, 104° C. or higher, or 105° C. or higher, and 125° C. or lower, 123° C. or lower, 120° C. or lower, 118° C. or lower, 115° C. or lower, 112° C. or lower, or 110° C. or lower (e.g., greater than 100° C. to 125° C., 101° C. to 123° C., 102° C. to 120° C., 103° C. to 118° C., 105° C. to 115° C., or 107° C. to 113° C.). When the glass transition temperature (T g ) is within the above range, when the polyester resin is strained at high temperatures, the polyester resin can recover quickly from the strain over time. As a result, the polyester resin can have high heat resistance and mechanical strength.
[0037] According to the present invention, the polyester resin can have a strain recovery rate (SR) controlled within a specific range. In particular, when a sample with a thickness of 1 mm prepared from the polyester resin is subjected to dynamic mechanical analysis (DMA), the strain recovery rate (SR) according to the following equation 2 can exceed 45%.
[0038] [Equation 2]
[0039] SR(%)={1–(S2–S0 / S1–S0)}×100
[0040] In Equation 2, S0 is the initial length of a sample with a thickness of 1 mm prepared from polyester resin, and S1 is the length of the sample after the sample is held under an applied force for 3 minutes so that the length of the sample is below the glass transition temperature (T g )30℃ temperature (T g S2 is the length of the sample measured when it is stretched by 3% at -30°C, and S3 is the length of the sample measured after the force applied to the sample is removed and the sample is left to stand for 5 minutes.
[0041] In particular, the strain recovery rate (SR) according to the above equation 2 may be 46% or more, 48% or more, 50% or more, 51% or more, 53% or more, 55% or more, 58% or more, 60% or more, 61% or more, 63% or more, 65% or more, 68% or more, or 70% or more (e.g., greater than 45% to 70%, 46% to 69%, 47% to 68%, 49% to 66%, 50% to 65%, or 52% to 63%). When the strain recovery rate (SR) is within the above range, the polyester resin has excellent properties of recovering from strain occurring at high temperatures, thereby providing a polyester resin having high mechanical strength.
[0042] As the content of 1,4-cyclohexanedimethanol contained in the diol component increases, or as the ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) in 1,4-cyclohexanedimethanol increases, the strain recovery rate (SR) tends to increase proportionally. In view of this, the present invention is characterized in that in order to improve the strain recovery rate (SR) to obtain a polyester resin with excellent heat resistance and mechanical strength, the content of 1,4-cyclohexanedimethanol and the ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) in 1,4-cyclohexanedimethanol are controlled. Here, 1,4-cyclohexanedimethanol can refer to virgin 1,4-cyclohexanedimethanol (virgin CHDM), recycled 1,4-cyclohexanedimethanol (recycled CHDM), or a combination thereof.
[0043] According to the present invention, polyester resin includes dicarboxylic acid repeating units derived from dicarboxylic acid component.Dicarboxylic acid component is not particularly limited, as long as it is a known dicarboxylic acid component.Especially, it may include at least one selected from the group consisting of terephthalic acid, recycled terephthalic acid, dimethyl terephthalic acid, isophthalic acid, dimethyl terephthalate, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid dimethyl ester, 1,3-cyclohexanedicarboxylic acid dimethyl ester, 2,6-naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, 4,4'-stilbene dicarboxylic acid, 2,5-furan dicarboxylic acid and 2,5-thiophenedicarboxylic acid.For example, dicarboxylic acid may include terephthalic acid, isophthalic acid, dimethyl terephthalate or a combination thereof.
[0044] According to the present invention, polyester resin includes the diol repeating unit derived from diol component.Diol component is not particularly limited, as long as it is known diol component.Especially, it can include at least one (for example, two or more, three or more or four or more) selected from the group consisting of: ethylene glycol, regenerated ethylene glycol, diethylene glycol, regenerated diethylene glycol, 1,4-cyclohexanedimethanol, regenerated 1,4-cyclohexanedimethanol, isosorbide, regenerated isosorbide, bis-2-hydroxyethyl terephthalate, regenerated bis-2-hydroxyethyl terephthalate, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-propylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-propylene glycol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol and their derivatives.
[0045] For example, the diol component may substantially include 1,4-cyclohexanedimethanol or regenerated 1,4-cyclohexanedimethanol. The content of 1,4-cyclohexanedimethanol or regenerated 1,4-cyclohexanedimethanol contained in the diol component is not particularly limited, but based on 100 mol% of the diol component, it may be 10 mol% to 90 mol%, in particular, 15 mol% to 85 mol%, 20 mol% to 80 mol%, 25 mol% to 78 mol%, 30 mol% to 75 mol%, 35 mol% to 74 mol%, 40 mol% to 73 mol%, 45 mol% to 72 mol%, or 50 mol% to 70 mol%. When the content of 1,4-cyclohexanedimethanol or regenerated 1,4-cyclohexanedimethanol is within the above range, a polyester resin whose strain recovery rate (SR) according to equation 2 is controlled to be within the desired range can be obtained. As a result, a polyester resin with excellent heat resistance and mechanical strength can be provided.
[0046] According to the present invention, 1,4-cyclohexanedimethanol includes a trans structural isomer, trans-1,4-cyclohexanedimethanol (trans-CHDM), and a cis structural isomer, cis-1,4-cyclohexanedimethanol (cis-CHDM). The present invention can provide a polyester resin with significantly enhanced heat resistance and mechanical strength by controlling the ratio of trans-CHDM at a high level. In particular, 1,4-cyclohexanedimethanol can include trans-CHDM and cis-CHDM in a content ratio (molar ratio) of 60:40 to 85:15. For example, the content ratio of trans-CHDM to cis-CHDM may be 62:38 to 83:17, 64:36 to 81:19, 65:35 to 80:20, 66:34 to 79:21, or 67:33 to 78:22. For example, the content of trans-CHDM in 1,4-cyclohexanedimethanol may be 60 to 85 mol%, 62 to 83 mol%, 64 to 81 mol%, 65 to 80 mol%, 66 to 79 mol%, or 67 to 78 mol%, based on 100 mol% of 1,4-cyclohexanedimethanol. Furthermore, the content of cis-CHDM in 1,4-cyclohexanedimethanol may be 15 to 40 mol%, 17 to 38 mol%, 19 to 36 mol%, 20 to 35 mol%, 21 to 34 mol%, or 22 to 33 mol%, based on 100 mol% of 1,4-cyclohexanedimethanol. When the content ratio (molar ratio) is within the above range, a polyester resin having excellent heat resistance, mechanical strength, and strain recovery rate at high temperatures can be provided.
[0047] 1,4-cyclohexanedimethanol can be obtained by isomerizing 1,4-cyclohexanedimethanol having a low cis-CHDM content to increase the trans-CHDM content by conventional methods. Alternatively, 1,4-cyclohexanedimethanol can be obtained by separating the cis-CHDM component using conventional methods to intentionally increase the trans-CHDM content. For example, 1,4-cyclohexanedimethanol can be obtained by increasing the trans-CHDM content by adding a basic catalyst to 1,4-cyclohexanedimethanol and applying heat thereto, by separating 1,4-cyclohexanedimethanol including trans-CHDM and cis-CHDM using a difference in boiling points, or by increasing the trans-CHDM content by hydrogenating a dialkyl 1,4-cyclohexanedicarboxylate.
[0048] At the same time, the diol component may include at least one (two or more, or three or more) selected from the group consisting of the following as a comonomer and 1,4-cyclohexanedimethanol: ethylene glycol, recycled ethylene glycol, isosorbide, recycled isosorbide, bis-2-hydroxyethyl terephthalate, recycled bis-2-hydroxyethyl terephthalate and 2,2,4,4-tetramethyl-1,3-cyclobutanediol. When the diol component includes a comonomer, a polyester resin with excellent heat resistance and mechanical strength and environmental friendliness can be provided. In particular, isosorbide is a biomaterial produced by a chemical method based on ingredients derived from plant resources such as corn. It has lower sensitivity to global warming potential (GWP) than other dicarboxylic acid components (such as terephthalic acid) or other diol components; therefore, the polyester resin prepared using it can emit significantly less greenhouse gases.
[0049] The content of ethylene glycol or regenerated ethylene glycol contained in the diol component is not particularly limited, but it may be 1 to 70 mol%, specifically, 5 to 65 mol%, 7 to 60 mol%, 9 to 55 mol%, 11 to 50 mol%, or 13 to 45 mol%, based on 100 mol% of the diol component.
[0050] The content of isosorbide or regenerated isosorbide contained in the diol component is not particularly limited, but it may be 1 to 50 mol%, specifically, 4 to 45 mol%, 7 to 40 mol%, 10 to 35 mol%, 13 to 30 mol%, or 16 to 25 mol%, based on 100 mol% of the diol component.
[0051] Meanwhile, the recycled monomers contained in the dicarboxylic acid component and the diol component (i.e., recycled terephthalic acid, recycled ethylene glycol, recycled diethylene glycol, recycled 1,4-cyclohexanedimethanol, recycled isosorbide, and recycled bis-2-hydroxyethyl terephthalate) may refer to recycled monomers obtained from used waste polyester resins or waste polyester products through a known depolymerization method. Even when such recycled monomers are used, the present invention can provide a polyester resin having excellent heat resistance and mechanical strength by optimizing the composition of the diol component.
[0052] According to the present invention, it can be confirmed that the polyester resin has high mechanical strength in terms of impact strength. For example, a sample with a thickness of 3.2 mm prepared from the polyester resin can have an impact strength of 800 J / m or higher. In particular, the impact strength can be 810 J / m or higher, 820 J / m or higher, 830 J / m or higher, 840 J / m or higher, or 850 J / m or higher (e.g., 800 J / m to 860 J / m, 820 J / m to 855 J / m, or 840 J / m to 853 J / m).
[0053] According to the present invention, the intrinsic viscosity (melt intrinsic viscosity) (IV) of the polyester resin may be 0.64 dl / g to 0.78 dl / g. Specifically, the intrinsic viscosity may be 0.64 dl / g to 0.77 dl / g, 0.65 dl / g to 0.77 dl / g, 0.65 dl / g to 0.76 dl / g, 0.66 dl / g to 0.75 dl / g, or 0.68 dl / g to 0.74 dl / g. When the intrinsic viscosity of the polyester resin is within the above range, articles having desired physical properties can be produced while ensuring the moldability of the polyester resin.
[0054] According to the present invention, when the degree of environmental impact (e.g., global warming potential; GWP) is evaluated by life cycle assessment (LCA), the polyester resin can be evaluated as environmentally friendly. Specifically, when measured according to ISO 14040 standard, the polyester resin can have greenhouse gas (GHG) emissions of 1.5 kg CO2 / kg or less, 1.3 kg CO2 / kg or less, 1.2 kg CO2 / kg or less, 1.1 kg CO2 / kg or less, 1.07 kg CO2 / kg or less, 1.05 kg CO2 / kg or less, 1.03 kg CO2 / kg or less, or 1.02 kg CO2 / kg or less.
[0055] Meanwhile, according to the present invention, the polyester resin may further include a component derived from at least one additive selected from an antioxidant, a branching agent, a colorant, a crystallizing agent, a catalyst, a stabilizer, and an ultraviolet absorber.
[0056] The antioxidant is not particularly limited, but may include at least one selected from the group consisting of hindered phenol-based compounds, phosphite-based compounds, and thioether-based compounds.
[0057] The branching agent may be a compound having three or more functional groups. In particular, it may include at least one selected from the group consisting of trimellitic anhydride, trimellitic acid, pyromellitic dianhydride, glycerol, trimethylolpropane, pentaerythritol, citric acid, tartaric acid, and 3-hydroxyglutaric acid.
[0058] The colorant is not particularly limited, but may include at least one selected from the group consisting of a cobalt-based compound, an anthraquinone-based compound, a cyclic ketone-based compound, an azo-based compound, and a methine compound. Specifically, the colorant may be cobalt acetate, cobalt propionate, Polysynthren Blue RLS toner from Clariant, and Solvaperm Red BB toner from Clariant.
[0059] The catalyst is not particularly limited, but may include methides of sodium and magnesium; acetates, borates, fatty acid salts, and carbonates of Zn, Cd, Mn, Co, Ca, and Ba; or oxides of Mg, Pb, Mn, Ti, Sb, Sn, Al, and Ge, or hydrates thereof. Specifically, the catalyst may be tetraethyl titanate, acetyl tripropyl titanate, tetrapropyl titanate, tetrabutyl titanate, 2-ethylhexyl titanate, octanediol titanate, triethanolamine titanate, acetylacetonate titanate, ethyl acetoacetate titanate, isostearyl titanate, titanium dioxide, germanium dioxide, germanium tetrachloride, ethylene glycol germanium, germanium acetate, or a combination thereof.
[0060] The stabilizer is not particularly limited, but may include phosphorus-based compounds such as phosphoric acid, trimethyl phosphate, and triethyl phosphate.
[0061] According to the present invention, the polyester resin may be in the form of chips, pellets or powder.
[0062] In addition, the polyester resin may be a homopolymer or a copolymer. In particular, the polyester resin may be selected from polyethylene terephthalate (PET), polyethylene terephthalate glycol (PETG), polyethersulfone (PES), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polyadipate-co-butylene terephthalate (PBAT), polyadipate-co-trimethylene terephthalate (PPAT), polycyclohexane dimethyl terephthalate (PCT) and thermoplastic polyester elastomer (TPEE).
[0063] Method for preparing polyester resin
[0064] As is generally known, the polyester resin according to the present invention can be prepared by an esterification reaction or an ester exchange reaction followed by a polycondensation reaction. In particular, the method for preparing the polyester resin according to the present invention may include feeding a diol component and a dicarboxylic acid component into a reactor (S-1); subjecting the diol component and the dicarboxylic acid component to an esterification reaction to prepare an oligomer (S-2); and subjecting the oligomer to a polycondensation reaction (S-3).
[0065] According to the present invention, step (S-1) is a step of feeding a diol component and a dicarboxylic acid component to a reactor. Since the diol component and the dicarboxylic acid component are the same as above, description thereof is omitted.
[0066] When the diol component and the dicarboxylic acid component are fed into the reactor, the feed molar ratio thereof (the number of moles of the diol component / the number of moles of the dicarboxylic acid component) is not particularly limited, but may be 1.05 to 1.30, 1.07 to 1.28, 1.09 to 1.26, 1.11 to 1.24, or 1.13 to 1.22 in view of the efficiency of the esterification reaction and the polycondensation reaction described later.
[0067] A batch reactor or a continuous reactor can be used as the reactor.
[0068] In addition, at least one additive selected from the group consisting of an antioxidant, a branching agent, a colorant, a crystallizing agent, a catalyst, a stabilizer, and an ultraviolet absorber may be further fed to the reactor.
[0069] According to the present invention, step (S-2) is a step of subjecting the diol component and the dicarboxylic acid component to an esterification reaction to prepare an oligomer. The conditions for conducting the esterification reaction may not be particularly limited.
[0070] Specifically, the temperature for conducting the esterification reaction may be 220° C. to 300° C., 225° C. to 290° C., 230° C. to 285° C., 235° C. to 280° C., 240° C. to 275° C., or 250° C. to 270° C. In addition, the pressure for conducting the esterification reaction may be 0.1 kgf / cm 2 Up to 5kgf / cm 2 , 0.1kgf / cm 2 Up to 4kgf / cm 2 , 0.3kgf / cm 2 Up to 3kgf / cm 2 , 0.5kgf / cm 2 Up to 2kgf / cm 2 or 1kgf / cm 2 Up to 2kgf / cm 2 When the esterification reaction is carried out under the above conditions, the generation of side reactants is minimized, while oligomers having a desired molecular weight can be obtained in high yield.
[0071] According to the present invention, step (S-3) is a step of subjecting the oligomer to a polycondensation reaction. The conditions for conducting the polycondensation reaction are not particularly limited.
[0072] In particular, the temperature for carrying out the polycondensation reaction may be 250° C. to 320° C., 255° C. to 310° C., 260° C. to 300° C., 265° C. to 290° C., or 270° C. to 285° C. In addition, the polycondensation reaction may be carried out under conditions lower than (reduced pressure) normal pressure (e.g., 1 atm). When the polycondensation reaction is carried out under the above conditions, a polyester resin (polymer) having crystallinity and ensuring moldability can be effectively produced.
[0073] Meanwhile, if necessary, the method for preparing the polyester resin according to the present invention may further include subjecting the reactant obtained by the polycondensation reaction in step (S-3) to a solid-state polymerization reaction in order to control the intrinsic viscosity (IV), molecular weight, etc. of the reactant. The solid-state polymerization reaction conditions are not particularly limited and can be appropriately set according to the intrinsic viscosity, molecular weight, etc. of the desired polyester resin.
[0074] Products
[0075] The articles according to the present invention are prepared from the polyester resin described above. In particular, the polyester resin can be subjected to a molding process to produce articles having various shapes and uses. Since these articles are prepared from the polyester resin described above, they can have excellent heat resistance and mechanical strength.
[0076] The method of molding the polyester resin to produce an article is not particularly limited as long as it is a generally known method. Specific examples include injection molding, extrusion molding, compression molding, vacuum molding, and blow molding.
[0077] These articles can be containers, films, sheets or indoor and outdoor materials. In particular, they can be food containers or packaging films that require high heat resistance and mechanical strength. DETAILED DESCRIPTION
[0078] The present invention will be described in more detail below with reference to embodiments. However, these embodiments are provided for illustrative purposes only, and the present invention is not limited thereto.
[0079] [Example 1]
[0080] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,494.4 g), ethylene glycol (EG, 149.1 g), 1,4-cyclohexanedimethanol (CHDM, 1,514.7 g), isosorbide (ISB, 745.9 g), a Ge catalyst (16.9 g), and a stabilizer (8.7 g). Next, the temperature of the reactor was raised to 270° C., and then heated at 270° C. and 0.5 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0081] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 280°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.65 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0082] [Example 2]
[0083] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,217.7 g), ethylene glycol (EG, 248.5 g), 1,4-cyclohexanedimethanol (CHDM, 1,365.9 g), isosorbide (ISB, 546.1 g), Ge catalyst (9.0 g) and stabilizer (3.8 g). Next, the temperature of the reactor was raised to 258° C., and then the reaction mixture was stirred at 258° C. and 2 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0084] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 270°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.75 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0085] [Example 3]
[0086] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,565.8 g), ethylene glycol (EG, 287.5 g), 1,4-cyclohexanedimethanol (CHDM, 1,224.2 g), isosorbide (ISB, 812.4 g), a Ge catalyst (12.5 g), and a stabilizer (2.8 g). Next, the temperature of the reactor was raised to 265° C., and then the reaction mixture was stirred at 265° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0087] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 270°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.65 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0088] [Example 4]
[0089] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,968.6 g), 1,4-cyclohexanedimethanol (CHDM, 1,982.9 g), 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCBD, 901.3 g), a Ge catalyst (15.7 g), and a stabilizer (1.8 g). Next, the temperature of the reactor was raised to 265° C., and then heated at 265° C. and 1.5 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0090] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 272°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.75 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0091] [Example 5]
[0092] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,486.0 g), 1,4-cyclohexanedimethanol (CHDM, 1,466.4 g), isosorbide (ISB, 699.7 g), regenerated bis-2-hydroxyethyl terephthalate (r-BHET, 380.4 g), a Ge catalyst (12.5 g), and a stabilizer (6.5 g). Next, the temperature of the reactor was raised to 265° C., and then heated at 265° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0093] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 275°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.73 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0094] [Comparative Example 1]
[0095] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 3,007.2 g), ethylene glycol (EG, 1,010.9 g), 1,4-cyclohexanedimethanol (CHDM, 782.6 g), isosorbide (ISB, 238.0 g), a Ge catalyst (6.1 g), and a stabilizer (1.4 g). Next, the temperature of the reactor was raised to 255° C., and then the reaction mixture was stirred at 255° C. and 2 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0096] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 265°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.75 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0097] [Comparative Example 2]
[0098] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,674.9 g), ethylene glycol (EG, 539.5 g), 1,4-cyclohexanedimethanol (CHDM, 812.1 g), isosorbide (ISB, 847.0 g), Ge catalyst (8.8 g) and stabilizer (3.3 g). Next, the temperature of the reactor was raised to 265° C., and then the reaction mixture was stirred at 265° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0099] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 275°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.64 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0100] [Comparative Example 3]
[0101] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,341.2 g), ethylene glycol (EG, 288.6 g), 1,4-cyclohexanedimethanol (CHDM, 974.9 g), isosorbide (ISB, 864.8 g), a Ge catalyst (10.3 g), and a stabilizer (2.5 g). Next, the temperature of the reactor was raised to 262° C., and then the reaction mixture was stirred at 262° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0102] The reactants were then transferred to a polycondensation reactor, where they were subjected to a polycondensation reaction (PA) at 270°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.60 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to produce a polyester resin.
[0103] [Comparative Example 4]
[0104] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,287.9 g), ethylene glycol (EG, 153.8 g), 1,4-cyclohexanedimethanol (CHDM, 1,647.3 g), isosorbide (ISB, 362.2 g), Ge catalyst (9.5 g) and stabilizer (4 g). Next, the temperature of the reactor was raised to 267° C., and then the reaction mixture was stirred at 267° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0105] The reactants were then transferred to a polycondensation reactor, whereupon a polycondensation reaction (PA) was conducted at 285°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.70 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a coolant and pelletized to an average weight of approximately 12 to 14 mg to prepare a polyester resin.
[0106] [Comparative Example 5]
[0107] A 10-liter reactor equipped with a tower and a condenser that can be cooled with water was charged with terephthalic acid (TPA, 2,596.1 g), ethylene glycol (EG, 77.6 g), 1,4-cyclohexanedimethanol (CHDM, 1,756.6 g), isosorbide (ISB, 570.8 g), a Ge catalyst (13.4 g), and a stabilizer (6.1 g). Next, the temperature of the reactor was raised to 263° C., and then the reaction mixture was stirred at 263° C. and 1 kgf / cm 2 The esterification reaction (ES) was carried out under pressure to obtain a transparent reactant.
[0108] The reactants were then transferred to a polycondensation reactor, whereupon a polycondensation reaction (PA) was conducted at 282°C while maintaining the reactor at a pressure lower than atmospheric pressure. When the intrinsic viscosity (IV) of the reactants in the polycondensation reactor reached 0.68 dl / g, the reactants were discharged to the outside of the polycondensation reactor to form strands. The strands were then solidified with a cooling liquid and pelletized to an average weight of approximately 12 to 14 mg to prepare a polyester resin.
[0109] [Test Example 1]
[0110] The polyester resins prepared in the examples and comparative examples were each analyzed by differential scanning calorimetry (DSC) to determine whether a melting point (T m Here, DSC analysis of the polyester resin was performed as follows.
[0111] DSC analysis apparatus: DSC 1 model of Mettler Toledo was used.
[0112] Sample preparation: Take about 6 mg-10 mg of polyester resin and place it in an aluminum pan.
[0113] Scanning conditions: The DSC curve was obtained by the following procedure: the temperature was increased from room temperature to 280°C at a rate of 10°C / min under a nitrogen atmosphere, the temperature was decreased to 30°C at a rate of -300°C / min, and then the temperature was increased again to 280°C at a rate of 2°C / min. Thereafter, the temperature at which the endothermic peak appeared during the temperature increase in the obtained DSC curve was defined as the melting point (T m In addition, the melting point (T m )Calculate the heat of fusion (ΔH).
[0114] [Test Example 2]
[0115] The polyester resins prepared in the examples and comparative examples were each injection molded at a temperature of 250°C to 300°C to prepare a sample having a thickness of 3 mm (17.5 mm long, 12.5 mm wide). Dynamic mechanical analysis (DMA) (TA Instruments Q800) was performed on the thus prepared samples in single cantilever mode at a rate of 10°C / minute from 30°C to 150°C to obtain a tan δ curve. The temperature at the maximum value (tan δ peak) of the obtained tan δ curve was then determined and defined as the heat resistance of the polyester resin.
[0116] [Test Example 3]
[0117] The polyester resins prepared in Examples and Comparative Examples were each injection molded at a temperature of 250° C. to 300° C. to prepare a sample having a thickness of 1 mm (17.5 mm in length and 12.5 mm in width). The samples thus prepared were subjected to dynamic mechanical analysis (DMA) (Q800 from TA Instruments) in stress relaxation mode, and the strain recovery rate (SR) was calculated according to the following equation 2.
[0118] [Equation 2]
[0119] SR(%)={1–(S2–S0 / S1–S0)}×100
[0120] In Equation 2, S0 is the initial length of a sample with a thickness of 1 mm prepared from polyester resin, and S1 is the length of the sample after the sample is held under an applied force for 3 minutes so that the length of the sample is below the glass transition temperature (T g ) is the length of the sample measured when stretched 3% at a temperature of 30°C, and S2 is the length of the sample measured after the force applied to the sample is removed and the sample is allowed to stand for 5 minutes.
[0121] [Test Example 4]
[0122] The polyester resins prepared in the examples and comparative examples were each injection molded at a temperature of 250°C to 300°C to prepare a sample having a thickness of 3.2 mm (63.3 mm long, 12.5 mm wide). The impact strength (J / m) thereof was measured according to ASTM D256 and evaluated according to the following standards. The impact strength was measured using a YASUDA SEIKI SEISAKUSHO No. 258 PC-S impact tester (product name) (hammer capacity: 2.75 J).
[0123] ○: Impact strength is 800 J / m or higher
[0124] ×: Impact strength less than 800 J / m
[0125] [Test Example 5]
[0126] The polyester resins prepared in Examples and Comparative Examples were each dissolved in o-chlorophenol (OCP) at a concentration of 0.12% at 100°C, and the intrinsic viscosity (IV, dl / g) was measured with an Ubbelohde viscometer in a thermostat at 35°C.
[0127] [Test Example 6]
[0128] The polyester resins prepared in Examples and Comparative Examples were each injection molded at a temperature of 250° C. to 300° C. to prepare a sample having a thickness of 1 mm (length 17.5 mm, width 12.5 mm). The moldability thereof was measured according to the following criteria.
[0129] ○: No resin melting occurs on the screw during injection molding
[0130] ×: Resin melting occurred on the screw during injection molding
[0131] The evaluation results of the above test examples are summarized in Tables 1 and 2 below.
[0132] [Table 1]
[0133]
[0134]
[0135] [Table 2]
[0136]
[0137] Referring to Tables 1 and 2 above, the polyester resins of Examples 1 to 5 according to the present invention have a high temperature at the tan δ peak, while the value of X×Y and SR are controlled within the range required by the present invention, so they have excellent heat resistance and mechanical properties. In addition, T m is controlled to 250° C. or lower; therefore, moldability is excellent. Therefore, when a product is manufactured using the polyester resin according to the present invention, it is expected that an environmentally friendly product having excellent heat resistance and mechanical strength can be produced with high efficiency.
[0138] In contrast, the polyester resins of Comparative Examples 1 to 5 have values of X×Y not controlled within the range required by the present invention, and thus have poor heat resistance, mechanical strength, or moldability. In particular, the polyester resins of Comparative Examples 1 to 3 have SR outside the range required by the present invention, and thus have very poor mechanical strength. In addition, the polyester resins of Comparative Examples 4 and 5 have excessively high T m , indicating poor formability.
Claims
1. A polyester resin comprising a diol repeating unit derived from a diol component; and a dicarboxylic acid repeating unit derived from a dicarboxylic acid component, wherein when the value of tan δ is measured by dynamic mechanical analysis (DMA), the temperature at the maximum value of tan δ (tan δ peak) is 100° C. or higher, and the following equation 1 is satisfied: [Equation 1] 30≤X×Y≤60 In Equation 1, X is the mole percentage of 1,4-cyclohexanedimethanol (CHDM) based on 100 mol% of the diol component, and Y is the molar ratio of trans-1,4-cyclohexanedimethanol (trans-CHDM) to the 1,4-cyclohexanedimethanol (CHDM).
2. The polyester resin according to claim 1, wherein the strain recovery rate (SR) according to the following equation 2 exceeds 45%: [Equation 2] SR(%)={1–(S2–S0 / S1–S0)}×100 In Equation 2, S0 is the initial length of a sample with a thickness of 1 mm prepared from the polyester resin, S1 is to keep the sample under the applied force for 3 minutes so that the length of the sample is below the glass transition temperature (T g ) is the length of the sample measured when stretched 3% at a temperature of 30°C, S2 is the length of the sample measured after the force applied to the sample is removed and the sample is left to stand for 5 minutes.
3. The polyester resin according to claim 1, wherein the melting point (T m ) does not appear, or its melting point (T m ) appears at 250℃ or lower. 4 . The polyester resin according to claim 1 , wherein the 1,4-cyclohexanedimethanol contained in the diol component includes trans-1,4-cyclohexanedimethanol (trans-CHDM) and cis-1,4-cyclohexanedimethanol (cis-CHDM) in a content ratio of 60:40 to 85:
15. 5 . The polyester resin according to claim 1 , wherein a sample having a thickness of 3.2 mm prepared from the polyester resin has an impact strength of 800 J / m or more. 6 . The polyester resin according to claim 1 , having an intrinsic viscosity (IV) of 0.64 to 0.78 dl / g.
7. The polyester resin according to claim 1, wherein the dicarboxylic acid component comprises at least one selected from the group consisting of terephthalic acid, recycled terephthalic acid, dimethyl terephthalic acid, isophthalic acid, dimethyl terephthalate, 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, dimethyl 1,4-cyclohexanedicarboxylate, dimethyl 1,3-cyclohexanedicarboxylate, 2,6-naphthalene dicarboxylic acid, diphenyl dicarboxylic acid, 4,4'-stilbene dicarboxylic acid, 2,5-furan dicarboxylic acid, and 2,5-thiophene dicarboxylic acid.
8. The polyester resin according to claim 1, wherein the diol component comprises at least one selected from the group consisting of ethylene glycol, recycled ethylene glycol, diethylene glycol, recycled diethylene glycol, 1,4-cyclohexanedimethanol, recycled 1,4-cyclohexanedimethanol, isosorbide, recycled isosorbide, bis-2-hydroxyethyl terephthalate, recycled bis-2-hydroxyethyl terephthalate, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-propylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, 2-methyl-1,3-propanediol, neopentyl glycol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, and derivatives thereof. 9 . The polyester resin according to claim 1 , wherein the diol component comprises 1,4-cyclohexanedimethanol in an amount of 45 mol % to 85 mol % based on 100 mol % of the diol component.
10. An article prepared from the polyester resin according to any one of claims 1 to 9.